Central and South America - Castellanos, Edwin J.; Lemos, Maria Fernanda; Astigarraga, Laura; Chacón, Noemí; Cuvi, Nicolás; Huggel, Christian; Miranda Sara, Liliana Raquel; Moncassim Vale, Mariana; Ometto, Jean Pierre; Peri, Pablo Luis; Postigo, Julio C.; Ramajo Gallardo, Laura; et al. (Cambridge University Press, 2022)
The chapter is divided into two main sections. The first section follows an integrative approach in which hazards, exposure, vulnerability, impacts and risks are discussed following the eight climatically homogeneous sub-regions described in WGI AR6 (Figure 12.1). The second section assesses the implemented and proposed adaptation practices by sector; in doing so, it connects to the WGII AR6 crosschapter themes. The storyline is then a description of the hazards, exposure, vulnerability and impacts providing as much detail as is available in the literature at the sub-regional level, followed by the identification of risks as a result of the interaction of those aspects. This integrated sub-regional approach ensures a balance in the text, particularly for countries that are usually underrepresented in the literature but that show a high level of vulnerability and impacts, such as those observed in CA. The sectoral assessment of adaptation that follows is useful for policymakers and implementers, usually focused and organised by sectors, government ministries or secretaries that can easily locate the relevant adaptation information for their particular sector. To ensure coherence in the chapter, a summary of the assessed adaptation options by key risks is presented, followed by a feasibility assessment for some relevant adaptation options. The chapter closes with case studies and a discussion of the knowledge gaps evidenced in the process of the assessment.